2003
DOI: 10.1177/0272431603023002003
|View full text |Cite
|
Sign up to set email alerts
|

Urban Adolescents' Transition to Junior High School and Protective Family Transactions

Abstract: This study explored the role of perceived family transactions of daily hassles, social support, and involvement with family in leisure activities in a sample of racially and ethnically diverse urban adolescents living in poverty as they made the transition to junior high school. Adolescents who perceived fewer daily hassles and more involvement with their families prior to the transition to junior high school appeared less vulnerable to declines in scores of self-esteem. In addition, adolescents who perceived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 69 publications
1
24
0
1
Order By: Relevance
“…In particular, investigations have included daily hassles from multiple domains, including those originating from family, work/school, and neighborhood contexts (e.g., Anthony and Nicotera 2008;Delongis et al 1982;Mayberry and Graham 2001;Rollins et al 2002). Furthermore, work with adolescent populations has demonstrated similar, albeit developmentally-appropriate dimensions (Compas et al 1987;Seidman et al 2003;Miller et al 2002). Given the increased mental health risk for females (in comparison to males) during adolescence (e.g., Hankin et al 2007), daily hassles may be an important step toward understanding adolescent females' short and long-term psychological functioning (Elgar et al 2003;Pinquart 2009).…”
Section: Daily Hassles and Psychological Functioningmentioning
confidence: 99%
“…In particular, investigations have included daily hassles from multiple domains, including those originating from family, work/school, and neighborhood contexts (e.g., Anthony and Nicotera 2008;Delongis et al 1982;Mayberry and Graham 2001;Rollins et al 2002). Furthermore, work with adolescent populations has demonstrated similar, albeit developmentally-appropriate dimensions (Compas et al 1987;Seidman et al 2003;Miller et al 2002). Given the increased mental health risk for females (in comparison to males) during adolescence (e.g., Hankin et al 2007), daily hassles may be an important step toward understanding adolescent females' short and long-term psychological functioning (Elgar et al 2003;Pinquart 2009).…”
Section: Daily Hassles and Psychological Functioningmentioning
confidence: 99%
“…Several studies, for example, have indicated that active coping approaches are less effective when stressors are uncontrollable, such as during parental divorce (Compas et al, 2001;Sandler, Reynolds, Kliewer, & Ramirez, 1992 Aber, 2003). These studies indicate that coping strategies associated with positive outcome for normative populations sometimes predict negative outcomes for low-income urban youth or youth of color.…”
Section: Stressful Contexts Affect Effectiveness Of Coping Responsesmentioning
confidence: 99%
“…Curiosamente, la actuación basada en la ayuda aparece negativamente asociada al hecho de acompañar a sus hijos a las actividades extraescolares de todo tipo, aspecto directamente relacionado con la autonomía del alumno (Seidman, Lambert, Allen y Aber, 2003) y que este grupo no captó dada su ausencia a varias sesiones del programa. La segunda variable, el control del tiempo de estudio en casa, aparece débilmente asociada al control de la asistencia a las clases, indicando que las sesiones del programa dedicadas a este aspecto, o bien no han surtido efecto, o bien han sido tratadas de modo inadecuado.…”
Section: Discusión Y Conclusionesunclassified